SALAK ORGANIK WONOSALAM: PRODUK INOVASI TEH DARI LIMBAH KULIT SALAK UNTUK UMKM DESA WONOSALAM KABUPATEN JOMBANG - Reynanda Bagus Widyo Astomo; Mochamad Angga Syahputra; Aida Mahmudah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2023)
Snakefruit rind which has been treated as waste has not been optimally processed, in fact it is only used as waste by the community, even though snakefruit peel can be reprocessed into herbal tea for snakefruit peel. Snakefruit skin has a high content of antioxidants and polyphenols. This service activity aims to introduce new innovative products from processed zalacca peels, namely herbal teas at Micro, Small and Medium Enterprises in Wonosalam Village, Jombang Regency. The main process for making tea from bark is drying at a temperature of 60 0C and drying time for 7 hours. This service activity was carried out in August 2022 at the Wonosalam Village community activity workshop and the introduction process was carried out at Micro, Small and Medium Enterprises for soft drink products in Sumber Hamlet, Wonosalam Village. The parameter used to differentiate the quality of herbal teas is the respondent's satisfaction index on the color, taste and aroma of herbal tea. Where the highest satisfaction is in bark tea with Screwpine aroma, which is as much as 75% of the total respondents.